A systematic review of the use of music interventions to improve outcomes for patients undergoing hip or knee surgery. (19th November 2018) - Sibanda, Annah; Carnes, Debra; Visentin, Denis; Cleary, Michelle
Abstract: Aim: To examine the effectiveness of music as an adjunct treatment for pain, anxiety, and/or postoperative delirium, for patients undergoing hip or knee surgery. Background: Patients undergoing hip or knee surgery are known to experience pain and anxiety before and after surgery and be prone to postoperative delirium. Design: Quantitative systematic review. Data Sources: CENTRAL, Embase, Ovid MEDLINE, CINAHL, and PsycINFO databases were systematically searched without time limits (to June 2018). Review Methods: A systematic search yielded 10 randomized controlled trials and quasi‐experimental designs. Studies were appraised using the Cochrane Risk of Bias Tool. Data were extracted using the Effective Practice and Organization of Care data extraction tool. Results: Mixed results were found for the effect of music on anxiety, pain, and postoperative delirium in patients undergoing hip or knee surgery. Six of 10 included studies provided evidence that music can improve anxiety, pain, or postoperative delirium outcomes for patients undergoing hip or knee surgery. Music effectively reduced anxiety in one of three studies. Three of seven studies reported benefits of music for reducing postoperative pain. Positive effects of music on postoperative delirium were reported in all three studies that evaluated this outcome. Within group improvements were observed in many of the studies. Conclusion: Music has the potential to improve outcomes of anxiety, pain, and postoperative delirium, for patients undergoing hip or knee surgery. The low number of studies found indicates results should be treated with caution. Further studies are required to provide strong evidence generalizable to a broader population. Abstract : 目的: 研究音乐作为髋关节或膝关节手术患者的疼痛、焦虑、及/或术后谵妄辅助治疗的效果。 背景: 众所周知, 接受髋关节或膝关节手术的患者会在手术前后感觉到疼痛和焦虑, 容易出现术后谵妄。 设计: 定量系统回顾。 数据来源: CENTRAL、Embase、Ovid MEDLINE、CINAHL和PsycINFO数据库, 系统搜索, 无时间限制(截至2018年6月)。 综述方法: 通过系统搜索获得10个随机对照试验和类试验设计。使用Cochrane风险偏倚工具对研究进行评估。采用Effective Practice and Organization of Care数据提取工具提取数据。 结果: 音乐对接受髋关节或膝关节手术患者的焦虑、疼痛、及术后谵妄的影响有好有坏。10项研究中有6项表明音乐可以改善接受髋关节或膝关节手术患者的焦虑、疼痛、及术后谵语。3项研究中有1项表明音乐能有效缓解焦虑。7项研究中有3项表明音乐有助减轻术后疼痛。在评估这一预后的三项研究中, 都有报道音乐对术后谵妄有积极影响。许多研究中都观察到组内改善。 结论: 音乐有可能改善接受髋关节或膝关节手术患者的焦虑、疼痛、及术后谵妄。研究数量较少, 说明应谨慎对待试验结果。需要进行进一步研究, 以提供能推广至更广泛人群的有力证据。